CERVANTES: an international randomized trial of radical surgery followed by adjuvant (chemo) radiation versus no further treatment in patients with early-stage, intermediate-risk cervical cancer (CEEGOG-CX-05; ENGOT-CX16). Issue 10 (13th September 2022) - Cibula, David; Borčinová, Martina; Kocian, Roman; Feltl, David; Argalacsova, Sona; Dvorak, Pavel; Fischerová, Daniela; Dundr, Pavel; Jarkovsky, Jiri; Höschlová, Eva; Slama, Jiri; Scambia, Giovanni
Abstract : Background: The role of adjuvant treatment in the intermediate-risk group of patients with early-stage cervical cancer is controversial and is supported by a single randomized Gynecologic Oncology Group (GOG) 92 study performed more than 20 years ago. Recent retrospective studies have shown excellent local control in this group of patients after radical surgery with no additional adjuvant treatment. Primary Objective: To evaluate if adjuvant (chemo)radiation is associated with a survival benefit after radical surgery in patients with intermediate-risk cervical cancer. Study Hypothesis: Radical surgery alone is non-inferior to the combined treatment of radical surgery followed by adjuvant (chemo)radiation in disease-free survival in patients with intermediate-risk cervical cancer. Trial Design: This is a phase III, international, multicenter, randomized, non-inferiority trial in which patients with intermediate-risk cervical cancer will be randomized 1:1 into arm A, with no additional treatment after radical surgery, and arm B, receiving adjuvant external beam radiotherapy±brachytherapy ± concomitant chemotherapy. Patient data will be collected over 3 years post-randomization of the last enrolled patient for primary endpoint analysis or for 6 years for the overall survival analysis. Major Inclusion/Exclusion Criteria: Patients with intermediate-risk early-stage cervical cancer (IB1–IIA), defined as lymph node-negative patients with a combination of negative prognostic factors (tumor size >4 cm; tumor size >2 cm and lymphovascular space invasion; deep stromal invasion >2/3; or tumor-free distance <3 mm) with squamous cell carcinoma or human papillomavirus (HPV)-related adenocarcinoma, are eligible for the trial. Primary Endpoint: Disease-free survival defined as time from randomization to recurrence diagnosis. Sample Size: 514 patients from up to 90 sites will be randomized. Estimated Dates for Completing Accrual and Presenting Results: It is estimated that the accrual will be completed by 2027 (with 3 additional years of follow-up) and primary endpoint results will be published by 2031. Estimated trial completion is by 2034. Trial Registration: NCT04989647 .